Doctors for Frontier Expansion: Japanese Physicians in Hawaii, 1868–1924. Issue 3 (1st September 2018) - Nishiyama, Takashi
Abstract: This article examines how frontier zone expansion and the migration of Asian professionals reinforced each other in complex and indirect ways. It focuses on Hawaii as a microcosm of transnationalism in medicine, analyzing its role as a host for licensed physicians from Japan, the United States, and other countries from 1868 to 1924. Looking beyond the context of a single East Asian country and East Asia as a region, or the East-West dichotomy, this study places all involved territories within the broader trans-Pacific arena to convey the sense of interconnectivity that human resources brought about between all the involved territories. The confluence of (geo)politics in Japan, East Asia, the Pacific, the United States, and the rest of the world molded intellectual migration in medicine from Japan to Hawaii, migration that served as an economically viable, diplomatically peaceful, and socially benign form of expansion.